RETRACTED: Critical safety climate dimensions for improved safety behavior: perspectives of construction workers - Chandra, Sathvik Sharath; Baghdadi, Ahmad; Shakor, Pshtiwan; Alsharef, Abdullah; Singh, Atul Kumar; Kineber, Ahmed Farouk (Frontiers in Built Environment, 2024)
Although extensive research has been conducted to explain the high accident rates in the Indian construction industry, studies focusing on the contributions of the prevailing safety climate as an enabler of such incidences remain sparse. Safety climate plays a crucial role in shaping workers' safety behaviors. Therefore, eliciting the perspectives of construction workers concerning safety climate dimensions that are critical for engendering improved safety behavior will provide valuable insights into the dimensions required to sustain the desired safety performance levels on construction sites. This study adopted a sequential mixedmethods research design. Purposively selected respondents and interviewees were surveyed and interviewed at various intervals. The study established that safety climate dimensions, such as effective leadership, effective communication, consultation, training, resources, incentives, and recognition, are critical in improving safety behavior among construction workers. The results of this study have significant implications for practice and knowledge, as they provide an approach for assessing the impact of different safety climate dimensions on the safety behavior of construction workers in India. Understanding these dimensions will lead to a framework for managing these challenges and improving construction safety performance.The study reported in this paper remains one of the few studies seeking to explore the impact of safety-climate dimensions on worker safety behavior in the construction industry.